Coordinate Variation in Lengths of Deoxyribonucleic Acid Molecules and Head Lengths in Morphological Variants of Bacteriophage T4 - Mosig, Gisela (1972)
We have investigated three classes of small bacteriophage T4 particles which differ from normal T4 particles in length of their deoxyribonucleic acid (DNA), in head length, in protein content, and in density. The different particles contain DNA molecules measuring 0.90, 0.77, or 0.67, respectively, of the normal T4 length. An additional class of viable particles contains DNA molecules of 1.1 unit length. These discrete differences in DNA length correspond to discrete differences in length (but not width) of the respective heads and are roughly proportional to the resulting differences in head volumes. The measured relative dimensions of the different heads fit best the relative dimensions predicted by a quasi-icosahedral model in which the smallest T4 head corresponds to an icosahedron with a triangulation number T = 21. The mid-portion of this structure is thought to be elongated by adding successive rows of gene 23 protein hexamers, the normal T4 head having three added rows. Different mutants produce small particles of the three classes in varying proportions, but no mutant produces exclusively particles of a single class. Particles of each class, with indistinguishable DNA content, show additional minor differences in protein content, as measured by differences in buoyant density and in the relative ratio of (32)P to (35)S.